2020
DOI: 10.1056/nejmoa2034577
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the BNT162b2 mRNA Covid-19 Vaccine

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the resulting coronavirus disease 2019 (Covid-19) have afflicted tens of millions of people in a worldwide pandemic. Safe and effective vaccines are needed urgently. Methods In an ongoing multinational, placebo-controlled, observer-blinded, pivotal efficacy trial, we randomly assigned persons 16 years of age or older in a 1:1 ratio to receive two doses, 21 days apart, of either placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

586
12,785
78
260

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13,214 publications
(14,550 citation statements)
references
References 8 publications
586
12,785
78
260
Order By: Relevance
“…Nonetheless, even with the limited number of reinfections, prior infection still confers a protective effect of 94% over the time of the study. This is equivalent to or better than the protection reported in recent vaccine studies 9,10 . The requirement to isolate (sometimes repeatedly) may adversely affect education, employment and mental health.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Nonetheless, even with the limited number of reinfections, prior infection still confers a protective effect of 94% over the time of the study. This is equivalent to or better than the protection reported in recent vaccine studies 9,10 . The requirement to isolate (sometimes repeatedly) may adversely affect education, employment and mental health.…”
mentioning
confidence: 53%
“…Further studies and longer surveillance are needed to confirm the duration of protection following previous SARS-CoV-2 infection, as well as the likelihood of subclinical infection and the impact of the evolution of new variants of the virus. In addition, as various national COVID-19 vaccination programmes get underway, it is important to remember that patients with prior SARS-CoV-2 antibodies were excluded from some of the vaccine studies 9,10 , and the efficacy of the vaccines on patients with prior immunity is unknown, and should perhaps be studied further.…”
mentioning
confidence: 99%
“…Following accelerated development, Phase 3 testing of some vaccine candidates is currently under way [16]. On the basis of data from the ongoing large-scale clinical trial [17], one of these vaccine candidates (BNT162b2) has been found to be effective and safe enough for the release of an emergency-use authorization (EUA) or equivalents in the United Kingdom (UK), Canada, and the USA at the beginning of December 2020. BNT162b2 and other vaccine candidates may soon be cleared for a similar emergency use in other countries, but there are limited data about long-term safety, efficacy in high-risk demographic groups, the magnitude of the protection, and the duration of the vaccine immunity [18,19].…”
Section: Commentarymentioning
confidence: 99%
“…[5][6][7] Global efforts to contain this deadly disease have led to the development of several vaccine candidates in different stages of clinical trials. 8 The efficacy results of two vaccines (Pfizer-BioNTech, Moderna) 9,10 have exceeded the World Health Organization preferred populationbased efficacy of 70% for a COVID-19 vaccine. 11 The US Food and Drug Administration (FDA) has authorized emergency use of these vaccines in the US population.…”
Section: Introductionmentioning
confidence: 99%